Penguasaan Konsep Siswa Melalui Sumber Belajar e-Modul Gerak Lurus dengan Software Flipbook Maker (UPEJ Unnes Physics Education Journal, 2020)
E-Modul is teaching materials with electronic devices for students to use which contain materials and learning activities. The purpose of this study was to determine the effectiveness of e-Modul on the subject of straight motion toward the learning outcomes of Grade X students. The study was conducted at MAN 2 Banjarnegara in Grade X science students. This research is a quasi-experimental research with Nonequivalent Control Group Design. Measurement of pretest-posttest in two different of treatment namely the experimental class to get learning use e-Module and the control class to get conventional learning. The results of this study indicate that the use of e-Modul subject to effective straight motion on mastery of the concept of straight motion students according to the results of the t test analysis showed an increase of 6.209 and the results of the analysis of the gain tests showed the use of e-Modules with an effective category of 0.510. In the control class from the results of the analysis of the test gain the effectiveness of conventional learning in the low category that is equal to 0.270. From this study it can be concluded that learning by using e-Module is a subject of effective straight-line motion toward the mastery of the concept of class X MAN 2 Banjarnegara students in the academic year 2017/2018. Learning e-Modules help students in the learning process both with the guidance of physics teachers or without the guidance of physics teachers. The use of e-modules increases student curiosity to write using the flipbook maker application to be able to make learning notes stored on mobile phones.